Researching creativity in education from ASEAN countries: bibliometric analysis - Nguyen, Tuan-Vinh; Tran, Viet-Nhi (International Journal of Evaluation and Research in Education (IJERE), 2025)
Creativity has emerged as a cornerstone of 21st-century education, particularly within Association of Southeast Asian Nations (ASEAN) countries striving to foster innovation and knowledge-based economies. This bibliometric study examines 453 publications on creativity in education across ASEAN from 2000 to 2024, utilizing Scopus data analyzed through Biblioshiny and VOSviewer. The findings reveal Indonesia as the dominant contributor (65% of publications), with scholars like Zubaidah and Corebima making significant contributions through highly cited works. Key journals, including “Thinking Skills and Creativity” and the “International Journal of Instruction”, have played crucial roles in disseminating ASEAN research globally. The thematic analysis identifies five major clusters centered on science, technology, engineering, and mathematics (STEM) integration, project-based learning, digital technologies, research methodologies, and professional development. Temporal network analysis demonstrates an evolution from discipline-specific approaches toward broader conceptualizations of creativity and an increased emphasis on technological integration. Despite these advances, the study identifies persistent challenges in cross-national collaboration, methodological consistency, and longitudinal research. This analysis provides strategic insights for educators, researchers, and policymakers in aligning educational practices with regional innovation goals while highlighting the need for enhanced research collaboration and standardized assessment tools.